(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article explores the revolutionary movements that emerged in Midnapore, a region historically significant for its role in India’s struggle for independence. Focusing on key figures, events, ideologies, and their impact on the socio-political landscape, the study provides a comprehensive overview of how Midnapore became a crucible for revolutionary fervor during the colonial era. The ideologies embraced by the revolutionary movements in Midnapore were diverse but shared a common goal of overthrowing British rule. Influenced by both Indian and international revolutionary thinkers, these groups advocated for armed struggle as a means to achieve independence. They sought to inspire mass uprising and disrupt colonial authority through targeted actions against symbols of British power. The revolutionary movements in Midnapore exemplify the spirit of defiance and sacrifice that characterized India’s struggle against colonialism. The legacy of these movements continues to resonate in contemporary narratives of nationalism and freedom across the subcontinent.